Pakistan : Report on Observance of Standards and Codes; Fiscal Transparency Module; An Update. (IMF Staff Country Reports; Country Report ;, 2008)
This study was carried out in association with an FAD technical assistance mission on public financial management issues. It focuses on transparency aspects of fiscal management reforms reviewed by that mission as well as implementation of key report on observance of standards and codes recommendations. A strong legal framework for coordinating fiscal and debt management policies and improving fiscal transparency by Fiscal Responsibility and Debt Limitation Law (FRDL) was also established. The update assesses the impact of these reforms that are under way and suggests priorities for further transparency improvements. Pakistan Improvement to Accounting and Auditing (PIFRA) has been implemented recently.